Exchange Rate Pass Through to Prices in Maldives - Masha, Iyabo (IMF Working Papers; Working Paper ;, 2012)
This study examines the degree of exchange rate pass through (EPRT) into producer and consumer prices in Maldives. ERPT to consumer prices is first estimated using a nonparametric approach. A recursive vector autoregression is then used to model both consumer and producer price changes. The nonparametric estimation indicates that ERPT to consumer prices is very high, both in absolute terms and relative to other countries. The dynamics of ERPT as derived from the empirical estimation indicate that ERPT to consumer and producer prices is significant but not complete, and that the impact of exchange rate changes persists into the second year.